The Movement of Muslimah Hizbut Tahrir Indonesia (MHTI) Against Feminism, 2000-2017 - Jamilatul Firdausi (An-Nisa' Journal of Gender Studies, 2023)
The Feminist movement became a forum to voice women's injustice which then caused social changes. However, some organizations oppose the understanding and movement of Feminism, one of them is Muslimah Hizbut Tahrir Indonesia (MHTI). This study aims to find out the rejection movements and thoughts of MHTI against Feminism. There are three things discussed, The first is the development history of Indonesia Muslimah Hizbut Tahrir (MHTI). The second is MHTI’s thoughts on the role of women, and the third is MHTI’s rejection of feminism. The method type of this research is the history method, these are heuristic, verification, interpretation, and historiography. This study results are MHTI was an HTI's autonomous organization that wished to establish an Islamic Caliphate based on Kaffah Islamic Syari’a. Then, MHTI argued that women's main role was to be housewives who are responsible for caring for children and fostering a harmonious family. MHTI firmly rejected feminism because it is considered as destroying the structure of men's and women's roles that had been determined in Islam. So, they acted in various regions to spread their ideas.